Effect of Fiber Loading on the Mechanical Strength of NFR Hybrid Composites - Tumolva, Terence; Kubouchi, Masatoshi; Aoki, Saiko; Sakai, Tetsuya (ASEAN Journal of Chemical Engineering, 2010)
Ortho-type UP resin is reinforced with long abaca and short bagasse fibers to produce a novel type of natural fiber-reinforced (NFR) hybrid composite material that is environment-friendly, has a long service life, possesses the properties of both long and short FRP’s, and has also acquired the advantages of utilizing two different types of natural fiber reinforcements. The abaca and bagasse fibers are treated in 5wt% NaOH(aq) solution at 80°C for 9 hours and pressed into continuous, unidirectional fiber sheets and random fiber mats, respectively. The fibers are then incorporated into the resin matrix by hand lay-up method, producing FRP laminates with the same uniform thickness but subjected to varying fiber loading conditions: (1) the stacking of long fiber sheets are done in cross-ply and parallel orientation; (2) the abaca and bagasse fibers are stacked in different alternating sequence patterns, and (3) the fibers are added into the ortho-UP matrix at increasing fiber fraction. The alkali-treated FRP laminates show an increase in fiber-matrix interfacial adhesion as compared to the untreated FRP’s, based on the overall improvement in the composite mechanical strength, as well as from the lesser visible fiber pull-out observed from SEM images on their fracture surfaces. Also, as expected, the tensile and flexural strengths of the abaca/bagasse hybrid FRP measures intermediate to those of abaca and bagasse FRP’s. The strength has also improved with increasing fiber content, although this increase has also caused an increased occurrence of void spaces that may consequently become detrimental to the NFR composite’s performance.